2016
DOI: 10.1016/j.csbj.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of anticancer peptides against MCF-7 breast cancer cells from the peptidomes of Achatina fulica mucus fractions

Abstract: Several reports have shown antimicrobial and anticancer activities of mucous glycoproteins extracted from the giant African snail Achatina fulica. Anticancer properties of the snail mucous peptides remain incompletely revealed. The aim of this study was to predict anticancer peptides from A. fulica mucus. Two of HPLC-separated mucous fractions (F2 and F5) showed in vitro cytotoxicity against the breast cancer cell line (MCF-7) and normal epithelium cell line (Vero). According to the mass spectrometric analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 28 publications
2
55
0
1
Order By: Relevance
“…The study of Teerasak et al revealed that two HPLC-separated fractions of Achatina fulica mucus decreased viability of mammary gland adenocarcinoma cells (MCF7) and epithelial cells (Vero) [ 6 ]. In fractions, were identified 16 putative cationic and amphipathic anticancer peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Teerasak et al revealed that two HPLC-separated fractions of Achatina fulica mucus decreased viability of mammary gland adenocarcinoma cells (MCF7) and epithelial cells (Vero) [ 6 ]. In fractions, were identified 16 putative cationic and amphipathic anticancer peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Extracts from tissues of H. aspersa Müller were shown to possess anticancer activity against breast cancer cells (Hs578T) [ 5 ]. Two fractions of mucus of another snail, the giant African snail Achatina fulica , decreased viability of breast cancer cells (MCF-7) [ 6 ]. In turn, the mucus of Actinia equina showed cytotoxic effect on human erythromyeloid leukemia-derived cells (K592) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We utilized the Balanced 1 (B1) and Balanced 2 (B2) datasets described previously [ 53 ] to generate a new dataset called the Tyagi-B dataset. In total, we obtained 450 ACPs (225 each from B1 and B2) and 450 non-ACPs (225 each from B1 and B2) by combining both the B1 and B2 datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Snail slime has become a remarkable ingredient in cosmetic products because it contains some biochemical substances, which have properties useful to skin care, such as alantoin, elastin, collagen and hyaluronic acid [5] . Furthermore, the slime has also been reported to have pharmacological activities including antibacterial activity [6,7] , antioxidant and regenerative properties [8] and anticancer property [9] . Interestingly, the slime extracted from Achatina fulica has been reported to heal incised wounds faster than self-healing can [10] .…”
mentioning
confidence: 99%